2021
DOI: 10.1002/agj2.20669
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term responses of soils and crops to gypsum application on organic farms

Abstract: Gypsum is a high calcium (Ca) and sulfur (S) containing mineral used to improve soil fertility and physical characteristics in organic cropping systems. However, evidence regarding short-term improvements in soil properties and increased crop yield is lacking. We conducted replicated experiments on 14 different organic dairy farm fields in five Ohio counties in 2017 and 2018. Our analysis evaluated short-term effects of gypsum application on (a) nutrient concentrations in soils and crop tissues, (b) yield of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…While a limited number of responsive sites measured grain S concentrations, no strong correlation was found between these two variables. This is not uncommon in this region as previous studies have reported no consistent grain yield response to an increase in grain S concentrations (Chen et al., 2008; Fleuridor et al., 2021). However, when both leaf and grain S increased, a yield response was observed, specifically in corn.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…While a limited number of responsive sites measured grain S concentrations, no strong correlation was found between these two variables. This is not uncommon in this region as previous studies have reported no consistent grain yield response to an increase in grain S concentrations (Chen et al., 2008; Fleuridor et al., 2021). However, when both leaf and grain S increased, a yield response was observed, specifically in corn.…”
Section: Resultsmentioning
confidence: 72%
“…Historically, S tissue analysis has been considered a better predictor compared to soil nutrient availability but the mid-season tissue analyses often limit the effectiveness of soil-applied fertilizer to prevent yield losses (Eriksen, 2015). Corn ear leaf response to S fertilization has been previously reported in a number of studies (Chaganti et al, 2019;Fleuridor et al, 2021;Gaibor, 2021;Sutradhar et al, 2017) but does not consistently correlate with grain yield increase.…”
Section: Evaluation Of Diagnostic Indicators Of Sulfur Responsementioning
confidence: 99%
“…In 2016, corn yield was highest in the unamended control soils compared to soils receiving amendments (Table 3), which might be due to agricultural practices as corn plots were frequently hand‐weeded that year (data not shown). Previous studies have reported no effect on corn yield when applying similar annual rates of gypsum in Ohio soils (Chaganti et al., 2021, 2019; Fleuridor et al., 2021). Average corn yield, across amendments, ranged between 66 and 77 bu ac −1 for the first 2 yr and increased from 127 to 175 bu ac −1 for the following 4 yr.…”
Section: Resultsmentioning
confidence: 87%
“…All amendments significantly increased soil extractable S (Table 2). Gypsum and epsom typically increase soil extractable S levels when applied (Chaganti et al., 2019; Dick et al., 2008; Fleuridor et al., 2021). Regarding base saturation (BS), gypsum and gypsum+Hi‐Cal lime amendments significantly increased Ca BS, whereas epsom and epsom+dolomite amendments significantly decreased Ca BS relative to the non‐amended control (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The authors found (i) no synergic effect of gypsum and lime on soil chemical properties, crop yield, and most leaf-tissue macronutrients; (ii) yield increments were minor for cereals (4%) than for soybean (14%) and were limited to just 25% of cereal crop seasons, and 40% for soybean; (iii) in the short term, gypsum raised more the exchangeable calcium content to 0.6 m soil depth than lime, but the latter presented more reductions in the soil acidity and extended residual effect (improved soil conditions for extended period), and (iv) the lime application to the soil surface under no-tillage lowered the subsoil acidity up to 0.6 m in the first year after its application, and improved soybean grain yield. Fleuridor et al (2021) indicated no yield improvements for maize, alfalfa (Medicago sativa), or alfalfa-mixed grasses after two years of gypsum application. However, gypsum consistently increased sulfur concentrations in soil and crop tissues as soon as five months after each gypsum application.…”
Section: Gypsum To Grains Cropsmentioning
confidence: 99%